ALAT PERAGA MODEL UTERUS UNTUK SIMULASI PERDARAHAN, KOMPRESI BIMANUAL INTERNA DAN PEMASANGAN KONDOM KATETER - Dian Kartikasari; Linda Yuliana Salawane (JOMIS (Journal of Midwifery Science), 2024)
Bimanual compression (BC) and uterine balloon tamponade (UBT) are skills that midwifery students should achieve in midwifery emergency care, especially in atonic post partum haemorrhage (PPH) treatment as WHO recommendation. BC is performed by applying internal lower uterine pressure on anterior fornix of the uterus. While UBT can be performed by inserting a condom loaded foley’s catheter into the uterus and filled with saline. The aim is to press the blood vessels in the uterine cavity. For bimanual compression practice in the laboratory, students usually use a rubbered uterus model that can be pumped to simulate a soft and hardened uterus, but this model cannot be used to insert UBT because there is no cavity inside. The aim of this research is to create a uterine model that can provide bleeding simulation and perform bimanual compression and UBT. The research method is research and development (R&D). The total sample was 30 respondent, involving lecturers and clinical perceptor of Midwifery Department Poltekkes Kemenkes Sorong. The data was analyzed by changing the qualitative value to quantitative using a Likert scale then calculating the average score and cenverting it back to a qualitative value. Feasibility analysis by calculating the total respondent's score compared to the ideal score. The research results showed that the mean value was 6.45, which means that respondents strongly agreed (range 6.15-7.00) that this model is feasible, with a feasibility percentage of 91.85%. It is expected that this product can improve students' skills in performing bimanual compression and UBT